MODEL ARSITEKTUR BISNIS, SISTEM INFORMASI DAN TEKNOLOGI DI BAKOSURTANAL BERBASIS TOGAF - Iyan Supriyana (Universitas Ahmad Dahlan, 2010)
The information technology (IT) is a necessary in BAKOSURTANAL to support business in relation with data and spatial information. Users will get the advantage through easy and fast access to data and spatial information. The important of the enterprise architecture (EA) to play a role to support company is proven because it provides technology and process structure which are fundamental aspects in IT strategy. Enterprise architecture framework (EAF) will accelerate and simplify the development of EA by ascertaining comprehensive coverage of solutions, ensuring the result of EA is always in line with the growth of enterprise. This paper explains the open group architecture framework (TOGAF) from several of EAF. The result shows that the most suitable EAF for BAKOSURTANAL in Blueprint development is by proposing EA model that covers business, information system, and technology architecture which are relied on recommended technical basics that is possible to be implemented